2000
DOI: 10.1046/j.1365-3164.2000.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of canine claw disease – a prospective study of 24 dogs

Abstract: The aetiology of claw disease in 24 dogs exhibiting only claw disease was investigated with cytologic examination of claw exudate, complete blood count (CBC), serum biochemistry panel, urinalysis, total thyroxine (tT4) concentration, antinuclear antibody (ANA) titre, bacterial culture and sensitivity testing, fungal culture, histopathology of claw biopsy samples and elimination diet. Abnormalities on the CBC, serum biochemistry panel and urinalysis were minor and nonspeci®c. Total T4 concentrations were within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 9 publications
(16 reference statements)
3
38
0
Order By: Relevance
“…3,5,[25][26][27]33,34 A syndrome first described by Scott et al 34 and named lupoid onychodystrophy by these authors showed histopathologic changes compatible with lupus erythematosus. However, in a subsequent prospective study of this syndrome, 25 no other systemic or cutaneous features of canine lupus erythematosus could be identified.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…3,5,[25][26][27]33,34 A syndrome first described by Scott et al 34 and named lupoid onychodystrophy by these authors showed histopathologic changes compatible with lupus erythematosus. However, in a subsequent prospective study of this syndrome, 25 no other systemic or cutaneous features of canine lupus erythematosus could be identified.…”
Section: Discussionmentioning
confidence: 98%
“…3,5,[25][26][27]33,34 A syndrome first described by Scott et al 34 and named lupoid onychodystrophy by these authors showed histopathologic changes compatible with lupus erythematosus. However, in a subsequent prospective study of this syndrome, 25 no other systemic or cutaneous features of canine lupus erythematosus could be identified. Furthermore, in that study, dogs with claw disease due to pyoderma and food adverse reaction showed the same histopathologic features described by Scott et al 34 These features included interface dermatitis, lymphocytic exocytosis, and hydropic degeneration of the basal cell layer, and the authors suggested that the observed interface dermatitis may be a reaction pattern of the canine claw matrix rather than being diagnostic for a particular etiology.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[1][2][3] Other diseases may involve the claw bed. [1][2][3] Other diseases may involve the claw bed.…”
Section: Commentsmentioning
confidence: 99%